The Effect of Fraud Heptagon Framework on Fraudulent Financial Statements: Evidence from Energy Sector Companies - Laila Diah Septiana; Atta Putra Harjanto (LPPM Institut Pendidikan Nusantara Global, 2026)
Fraudulent financial statements pose a significant threat to the integrity of financial information and stakeholder trust, often reflecting unresolved agency conflicts between principals and agents. From an agency theory perspective, fraudulent reporting may arise when accounting-based monitoring mechanisms fail to constrain managerial behavior effectively. Using the fraud heptagon framework as an empirical proxy of monitoring weaknesses within agency relationships, this study analyzes the determinants of fraudulent financial statements. The population of this study comprises companies listed on the Indonesia Stock Exchange (IDX) and classified in the energy sector based on the Thomson Reuters Business Classification in the Refinitiv database for the period 2020–2024. Purposive sampling was employed, resulting in 250 analysis units. Unbalanced panel data were analyzed using panel data regression with EViews 12. The results indicate that only certain fraud heptagon factors act as determinants of fraudulent financial statements, namely pressure and collusion, which exhibit a positive effect. In contrast, opportunity, rationalization, capability, arrogance, and coercion do not significantly influence fraudulent financial statements. These findings suggest that several fraud heptagon elements are more closely related to behavioral characteristics and are not directly reflected in financial reporting data, highlighting the importance of effective accounting-based monitoring in mitigating agency conflicts.